Process parameter optimization for tensile strength and Hardness of Al-MMC using RSM technique. (2022) - Gugulothu, Bhiksha; Seetharaman, Suresh; Vijayakumar, S.; Jenila Rani, D.
Abstract: This study mainly focused to investigate the mechanical properties such as tensile strength(TS) and Hardness (HV) of 5083 Aluminum alloy prepared through stir casting method. Two reinforced materials in the form of powder to be adding with Al5083 for improving properties. Response surface methodology (RSM) is the mathematical technique which involves for optimization process on TS and HV and also helps to find better sample. As per central composite design (CCD), Totally 20 samples have been produced with variation of stirrer speed(A), Stir time (B) and Temperature (C).The experimental results revealed that TS was increased from 126Mpa to 178Mpa. Similarly, Hardness also raised to 85HV.finally, optimization analysis of all input process parameters and output responses were carried out with design expert software.